The role of oil prices in the euro area economy since the 1970s - Elke Hahn; Ricardo Mestre (European Central Bank (ECB), 2011)
This paper explores the role of oil prices in the euro area economy since the 1970s by applying a VAR framework with time varying parameters and stochastic volatility in which oil supply and global demand shocks are identified. Our results show that both types of shock contributed substantially to the oil price surges during historical oil crises and likewise to those over the past decade. Counterfactual histories of the price and activity variables, moreover, reveal much larger adverse contributions of both shocks to HICP inflation and GDP in the first half of the sample than in the second, which suggests that changes related to these shocks have contributed to the Great Moderation. Impulse responses, moreover, show that a decline in the pass through of the two shocks has added to the moderating contribution over time, while variance decompositions indicate no change in the relative importance of the two shocks overtime.
Keywords: E3; 330; euro area; Great Moderation; Oil prices; stochastic volatility; time varying parameter VAR model